2018
DOI: 10.1111/bcpt.13113
|View full text |Cite
|
Sign up to set email alerts
|

Impaired participation of potassium channels and Na+/K+ATPase in vasodilatation due to reduced nitric oxide bioavailability in rats exposed to mercury

Abstract: Mercury intoxication is a public health risk factor due to its hazardous effect to several organs, including the cardiovascular system. There is evidence of endothelial dysfunction after exposure to mercury, but the effects on endothelium-dependent vasodilatation are still unknown. In the present study, we aimed to evaluate the chronic effects of high HgCl doses on the mechanisms of vasodilatation. Wistar rats were injected with HgCl (1st dose 10.86 μg/kg, and daily doses 0.014 μg/kg for 30 days i.m.), and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…It has been previously reported that alterations in eNOS gene increase the susceptibility to cardiovascular diseases in individuals after Hg exposure by modulating NO levels ( de Marco et al, 2012 ). Exposure to Hg at low concentrations has deleterious vascular effects on aorta, coronary and basilar arteries related to greater vascular reactivity caused by the reduction of NO bioavailability in these vessels ( Wiggers et al, 2008 ; Peçanha et al, 2010 ; Botelho et al, 2019 ). Moreover, a study in mesenteric arteries from rats exposed for 30 days to HgCl 2 showed eNOS protein expression upregulation possibly due to a compensatory mechanism against metal-induced endothelial dysfunction ( Wiggers et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that alterations in eNOS gene increase the susceptibility to cardiovascular diseases in individuals after Hg exposure by modulating NO levels ( de Marco et al, 2012 ). Exposure to Hg at low concentrations has deleterious vascular effects on aorta, coronary and basilar arteries related to greater vascular reactivity caused by the reduction of NO bioavailability in these vessels ( Wiggers et al, 2008 ; Peçanha et al, 2010 ; Botelho et al, 2019 ). Moreover, a study in mesenteric arteries from rats exposed for 30 days to HgCl 2 showed eNOS protein expression upregulation possibly due to a compensatory mechanism against metal-induced endothelial dysfunction ( Wiggers et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with antioxidant compounds (including tiron and vitamin C) has proved effective in re-establishing blood vessel dilatation in environments of high oxidative stress. 15,42 Vascular GSH levels were determined to ascertain whether there were differences in its depletion in the trained or sedentary rats after PAR exposure. Some studies have shown an increase in lipid peroxidation and a decrease in GSH in the blood and target organs like the kidney and liver of PAR-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in order to confirm if decreased relaxation after PAR treatment is mediated by increased oxidative stress, isolated arteries were treated with antioxidant tiron, which normalized the relaxation response to both ACh and SNP. Treatment with antioxidant compounds (including tiron and vitamin C) has proved effective in re‐establishing blood vessel dilatation in environments of high oxidative stress 15,42 …”
Section: Discussionmentioning
confidence: 99%
“…The reactivity assay for thoracic aorta was performed as detailed elsewhere 19 . The artery was divided into cylindrical segments of 4 mm in length and vertically mounted in organ baths for large vessels containing modified Krebs‐Henseleit solution (in mmol/L: NaCl 127; KCl 4.7; CaCl 2 .2H 2 O 2.5; MgSO 4 .7H 2 O 1.2; KH 2 PO 4 1.17; NaHCO 3 24; Glucose 5 and EDTA 0.01) heated to 36 ± 0.5ºC and aerated with 95% O 2 and 5% CO 2 , keeping the pH at 7.4.…”
Section: Methodsmentioning
confidence: 99%